Tunable Thermal‐Sensitive Polymer–Graphene Oxide Composite for Efficient Capture and Release of Viable Circulating Tumor Cells. Issue 24 (26th April 2016) - Yoon, Hyeun Joong; Shanker, Apoorv; Wang, Yang; Kozminsky, Molly; Jin, Qu; Palanisamy, Nallasivam; Burness, Monika L.; Azizi, Ebrahim; Simeone, Diane M.; Wicha, Max S.; Kim, Jinsang; Nagrath, Sunitha
Abstract : A highly sensitive microfluidic system to capture circulating tumor cells from whole blood of cancer patients is presented. The device incorporates graphene oxide into a thermoresponsive polymer film to serve as the first step of an antibody functionalization chemistry. By decreasing the temperature, captured cells may be released for subsequent analysis.